(untitled) (Kerala Journal of Psychiatry, 2019)
BACKGROUND: Adolescent substance use is an important public health problem because of its potential consequences on a growing brain. Problematic internet use is also a related phenomenon. The validity of self-report of substance and internet use is questionable in this population because of social desirability bias. OBJECTIVE: To estimate gender specific extent of substance use and internet use among students of eighth to twelvth classes in an urban area in Ernakulam, Kerala based on the report of peers. MATERIALS AND METHODS: A school based cross-sectional study was conducted over a period of one month in Kalamassery, Ernakulam District, Kerala. Information on the extent of substance and internet use among the students was obtained by a peer-reported anonymous self- administered questionnaire from all the students of classes eighth to twelvth of three randomly selected schools. RESULTS: Data were collected from 278 school students (133 boys and 145 girls). Excessive Internet use was reported among 20% boys and 14% girls. Substances with high use among boys were nicotine (11.54%), cannabis (6.67%), solvent (5.88%) and alcohol (5.88%). Solvent use was reported among 2.77% of girls. CONCLUSION: Although peer report survey has certain limitations, it can give early indications of student behaviours. The estimates obtained are nearer to self-reported substance use. The reported solvent use in the study is worth exploring.